Advanced regenerative strategies for human knee meniscus - Cengiz, I. F. (2017)
The meniscus tissue has important roles in the function and biomechanics of the knee. Despite the great advances in the treatment of meniscus lesions, the clinical need is still not fulfilled. To overcome the challenges of regeneration, tissue engineering-based strategies have been attempted with limited success. The process of meniscus tissue regeneration is very complex and has many parameters that are evident only to a certain degree. Today, the regenerative strategies have been advancing beyond the traditional tissue engineering concept by growing the utilization of the expertises of complementary areas that include, but not limited to, bioreactor engineering, bioprinting coupled to reverse engineering, biology, nanotechnology and gene therapy approaches. Herein, the recent reported advanced strategies involving bioreactors, self-assembling process, and somatic gene therapy for meniscus regeneration are overviewed.